2020
DOI: 10.30699/jambs.28.126.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and the Intake of Trace Elements in People with Hypertension: A Cross-Sectional Study

Abstract: 10.30699/jambs.28.126.1 Background & Objective: Dietary patterns and the consumption of some macronutrients could influence hypertension as a public health problem. This study was conducted to identify dietary patterns and compare the intake of some micronutrients, as well as food groups, according to the Dietary Approach to Stop Hypertension (DASH) guidelines. Materials & Methods: This cross-sectional study assessed the dietary patterns of 101 people with mild to moderate hypertension who were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
(6 reference statements)
0
8
1
Order By: Relevance
“…It would also be worth investigating the effect of neuromuscular electrical stimulation (NMES; a passive type of exercise) protocols, such as in the study by Jandova et al [88], on circulating irisin, which could offer an alternative mode of exercising for people with difficulties maintaining a physically active life. In terms of aerobic training, Morteza et al [87] reported no significant changes for circulating irisin, which is contrary to our findings. Instead, we report on decreases in circulating irisin in blood following resistance training in normal weighted older males [76] and after high-repetition resistance training in healthy older adults [73].…”
Section: Summary Of Main Results and Interpretationscontrasting
confidence: 99%
See 1 more Smart Citation
“…It would also be worth investigating the effect of neuromuscular electrical stimulation (NMES; a passive type of exercise) protocols, such as in the study by Jandova et al [88], on circulating irisin, which could offer an alternative mode of exercising for people with difficulties maintaining a physically active life. In terms of aerobic training, Morteza et al [87] reported no significant changes for circulating irisin, which is contrary to our findings. Instead, we report on decreases in circulating irisin in blood following resistance training in normal weighted older males [76] and after high-repetition resistance training in healthy older adults [73].…”
Section: Summary Of Main Results and Interpretationscontrasting
confidence: 99%
“…Especially, the older adult female population would benefit from this protective effect as they are prone to osteoporosis. Cosio et al [86] and Morteza et al [87] also showed greater increases of circulating irisin in older adults after resistance training programs. It would also be worth investigating the effect of neuromuscular electrical stimulation (NMES; a passive type of exercise) protocols, such as in the study by Jandova et al [88], on circulating irisin, which could offer an alternative mode of exercising for people with difficulties maintaining a physically active life.…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 90%
“…The socio-demographic characteristics of the included studies are summarized in Table 1 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Fourteen studies were conducted in the U.S. [ 14 , 20 , 21 , 27 , 29 , 30 , 36 , 38 , 39 , 41 , 43 , 48 , 49 ,…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to the DASH diet was assessed using the tool constructed by Fung et al (2008) [ 51 ] in 28 studies [ 15 , 16 , 17 , 18 , 19 , 20 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 49 , 50 ] and the tool developed by Mellen at al. (2008) [ 52 ] in three studies [ 14 , 39 , 48 ], while one study [ 25 ] implemented the tool by Valipour et al (2017) [ 53 ], one study [ 34 ] implemented the tool by Lee et al (2017) [ 54 ], one study [ 21 ] implemented the tool by Folsom et al (2007) [ 55 ], one study [ 44 ] utilized principal component analysis (PCA) by Fransen et al, (2014) [ 56 ] and two studies [ 22 , 37 ] developed their DASH Score based on the guidelines produced by the National Institutes of Health and the National Heart Lung and Blood Institute (2018) [ 57 ]. Moreover, 18 studies [ 14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation